Design, Identification and Anti-Bacterial activity of New Tropylated Heterocycles - MuathJabbarTarfa Al-Abbasee; Taiseer Saleh; Ahmed Khalid Hussein; Suha Abdullah Hussein AlHaddad (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This work highlights design some modern tropylated five and six substituted pyrazole and dihydropyridine hetero cyclic derivatives. These derivatives obtained by efficient one pot reaction, this one involve direct N-tropylation of substituted pyrazole and dihydropyridine derivatives in conventional alcoholic solvent under reflux condition. The chemical structures of novel designed forms proved through FT-IR, 13C-NMR, CHNS elemental analysis and anti-bacterial activity.